Perceived Best Practices for Faculty Training in Distance Education - Michael G. McVey (Adult Education Research Conference, 2014)
After conducting a literature review of adult student learning styles and teaching method analysis, it became apparent that there was not a significant difference in academic performance for students with differing learning styles whether they attended face-to-face or online classroom environments. What was not clearly indicated though, from the review of the literature, was what were the perceived best practices for online teaching from the perspective of experienced distance educators and whether the instructors’ perceived learning style was incorporated in training programs to assist faculty to teach online. Thus, the purpose of this qualitative pilot study is to determine the perceived best practices to train faculty to teach in an online environment and how individual instructors’ perceived learning styles can be incorporated within best practices to foster competence on an individual instructor level. This study also analyzes faculty resistance to distance education and how transformative learning theory may play a role in overcoming this resistance.